2019
DOI: 10.1111/1750-3841.14489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dipping and Vacuum Impregnation Pretreatments on the Quality of Frozen Apples: A Comparative Study on Organic and Conventional Fruits

Abstract: The effect of dipping and vacuum impregnation (VI) pretreatments with lemon juice solution on the quality and stability of organic and conventional frozen apples was investigated. Fresh apples were characterized; organic apples showed, at equal starch and ripeness index, a lower sugar content, and higher acidity than conventional ones. The polyphenol content was slightly higher in organic apples than in conventional ones while polyphenoloxidase activity was similar. No differences in color and firmness were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, caffeic acid was shown to react with PPO by forming a caffeoyl-PPO complex, which is very slowly transformed in quinone, leaving a small part of the enzyme available for the binding with other phenol substrates (Janovitz-Klapp et al, 1990). Finally, as reported by Neri et al (2019), ORG apples showed after processing a higher firmness than CONV ones, which implies differences in mechanical strength between the tissues and, consequently, different cell responses toward physical damages induced by VI and/or freezing and frozen storage. Freezing may determine, in fact, cellular disruption, thus improving the extraction of analytes (Blanda et al, 2008).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Moreover, caffeic acid was shown to react with PPO by forming a caffeoyl-PPO complex, which is very slowly transformed in quinone, leaving a small part of the enzyme available for the binding with other phenol substrates (Janovitz-Klapp et al, 1990). Finally, as reported by Neri et al (2019), ORG apples showed after processing a higher firmness than CONV ones, which implies differences in mechanical strength between the tissues and, consequently, different cell responses toward physical damages induced by VI and/or freezing and frozen storage. Freezing may determine, in fact, cellular disruption, thus improving the extraction of analytes (Blanda et al, 2008).…”
Section: Resultsmentioning
confidence: 81%
“…The reduction of the PPO activity is due to the organic acids contained in the impregnant/dipping solution and, in particular, to the citric acid, which exerts a specific inhibitory effect on PPO (Zhou et al, 2016). In general, the ORG apples showed a decrease of the PPO activity higher than the CONV ones due to their higher citric acid uptake during pre-treatments (3.5 vs 3.1 mg g -1 dm in DIP samples and 4.8 vs 4.5 mg g -1 dm in VI_L ones) due to their higher porosity (Neri et al, 2019).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…These discrepancies were also found irrespective of the method of analysis used to determine the AOA and could depend on process-related factors such as the thawing methods and wounding [139,140] and/or on factors related to the raw material. In fact, the cultivar, the cultivation method, the ripening degree, the harvest season and pre-harvest or postharvest chilling stresses can significantly affect the composition of plant tissues and, thus, their mechanical strength [141] and response to physical stresses induced by processing, with effects on the release and oxidation of polyphenols after freezing and thawing [22,73,142]. In particular, these variables influence the composition of plant foods by affecting (i) the content of proteins and of sugars, which act as natural cryoprotectants [143], (ii) the phenolic content and composition due to the shift of the pathways involved in their biosynthesis [139,[144][145][146] and the concentration of oxidase enzymes, such as polyphenoloxidase, whose activity is affected not only by the total polyphenol content but also by the content of single polyphenols and/or by their oxidation products [147].…”
Section: Combined Effect Of Freezing and Frozen Storagementioning
confidence: 99%